Architects of political change : constitutional quandaries and social choice theory - Schofield, Norman, 1944- (Political economy of institutions and decisions., 2006)
This analysis builds on earlier theoretical work by Mancur Olson, William Riker and Douglass North. Professor Schofield emphasizes that under some conditions architects of political change can put a new perspective on societal quandaries, such that societies can choose an option that has a better 'probability of a fit choice'.